Radial and ulnar medullary canal diameter in children: Anatomical limitations of elastic stable intramedullary nailing - Wang, Cui; Su, Yuxi (Frontiers in Surgery, 2022)
Introduction: Surgery is inevitable for children who cannot achieve the ideal reduction in forearm fractures. The biggest limitation for elastic stabile intramedullary nailing (ESIN) fixation method is the size of the medullary canal diameter. We aim to measure the medullary canal diameter of the radius and ulnar at different ages in children. Methods: Forearm radiographs were retrospectively reviewed in 540 children. All background characteristics were measured and recorded including weight, sex, maturity of the radius and ulnar, and length of the radius and ulnar. Children with radius and ulnar diameters less than 2 mm were analyzed by regression statistical analysis by SPSS software. Results: When we set 2 mm as the minimum medullary canal diameter, our results showed that patients between the age of 3-12 years had radius and ulnar diameters under this limit. The regression analysis of risk factors with the 2 mm diameter limitation had significant differences based on age (P =0.006) and sex (P =0.033). There was no significant difference between patients based on weight (P =0.056), ulnar length (P =0.946), radius length (P =0.503), radius maturity (P =0.655), or ulnar maturity (P =0.774). Conclusions: The average medullary canal diameter remained steady until 12 years of age. However, the average diameter length did not significantly increase after age 12. The incidence of medullary canal diameter less than 2 mm is correlated with age and sex. Our results suggest that surgeons should pay attention to the medullary diameter of the anteroposterior and lateral radiographs to determine ESIN diameter size.